THE INFLUENCE OF LEARNING READINESS AND CONCENTRATION ON THE LEARNING OUTCOMES OF BUDDHIST RELIGIOUS EDUCATION AMONG TENTH-GRADE STUDENTS AT SMK KASIH MAITREYA SELATPANJANG, RIAU - Metta Theora; Mettadewi Wong; Isomudin (Jurnal Agama Buddha dan Ilmu Pengetahuan, 2026)
This study examines the influence of learning readiness and concentration on the learning outcomes of Buddhist Religious Education among tenth-grade students at SMK Kasih Maitreya Selatpanjang, Riau. The background of the research lies in the recognition that internal student factors are essential for successful learning, particularly in spiritual and value-based subjects. A quantitative survey method was applied, involving 99 students selected through total sampling. Research instruments consisted of validated and reliable questionnaires, and the data were analyzed using both simple and multiple linear regression. The findings revealed that: (1) learning readiness has a positive and significant influence on learning outcomes with a contribution of 68.5%; (2) concentration also positively and significantly affects learning outcomes with a contribution of 83.6%; (3) jointly, both variables strongly influence learning outcomes with a combined contribution of 84.4%; and (4) concentration is the most dominant predictor. These results confirm that readiness and concentration are crucial in supporting the academic performance of students in Buddhist Religious Education. Moreover, the findings highlight the relevance of Buddhist values such as mindfulness (sati), right effort (viriya), and calmness (samādhi) as guiding principles for enhancing students’ learning processes.